EFEK HARI PERDAGANGAN TERHADAP RETURN DAN VOLATILITASNYA PADA SAHAM INDEKS LQ45 DI BURSA EFEK INDONESIA - Najmudin, Najmudin; Jaryono, Jaryono (Performance, 2010)
This research aims to 1). test and determine trading day having return which highest and lowest, 2). test the effect of trading days on stock return, and 3). determine trading day having highest and lowest volatility by using three models: OLS, GARCH ( 1,1), and GARCH-M ( 1,1). By using the daily price data of stocks listed at LQ45 index, the study obtains results that 1). There is no return which is lowest at bourse trading days, while return which is highest happened at Friday, 2). Trading days have effect to return stock, and 3). Five trading days in Indonesia Stock Exchange have the same volatility.